Using a High-Speed Movie Camera to Evaluate Slice Dropping in Clinical Image Interpretation with Stack Mode Viewers. - Yakami, Masahiro; Yamamoto, Akira; Yanagisawa, Morio; Sekiguchi, Hiroyuki; Kubo, Takeshi; Togashi, Kaori (Journal of Digital Imaging, 2013)
The purpose of this study is to verify objectively the rate of slice omission during paging on picture archiving and communication system (PACS) viewers by recording the images shown on the computer displays of these viewers with a high-speed movie camera. This study was approved by the institutional review board. A sequential number from 1 to 250 was superimposed on each slice of a series of clinical Digital Imaging and Communication in Medicine (DICOM) data. The slices were displayed using several DICOM viewers, including in-house developed freeware and clinical PACS viewers. The freeware viewer and one of the clinical PACS viewers included functions to prevent slice dropping. The series was displayed in stack mode and paged in both automatic and manual paging modes. The display was recorded with a high-speed movie camera and played back at a slow speed to check whether slices were dropped. The paging speeds were also measured. With a paging speed faster than half the refresh rate of the display, some viewers dropped up to 52.4 % of the slices, while other well-designed viewers did not, if used with the correct settings. Slice dropping during paging was objectively confirmed using a high-speed movie camera. To prevent slice dropping, the viewer must be specially designed for the purpose and must be used with the correct settings, or the paging speed must be slower than half of the display refresh rate.